Mucinous cystadenoma of the renal parenchyma presenting as a Bosniak IIF complex renal cyst. Issue 2 (18th January 2023) - Nate, Takanori; Hatano, Koji; Kato, Taigo; Kawashima, Atsunari; Abe, Toyofumi; Fukuhara, Shinichiro; Uemura, Motohide; Kiuchi, Hiroshi; Imamura, Ryoichi; Nonomura, Norio
Abstract : Introduction: A primary retroperitoneal mucinous cystadenoma should be surgically resected because of the risk of malignant transformation. However, mucinous cystadenoma of the renal parenchyma is very rare, and preoperative imaging mimics complicated renal cysts. Case presentation: A 72‐year‐old woman presented with a right renal mass on computed tomography that was followed up as a Bosniak IIF complicated renal cyst. One year later, the right renal mass gradually increased in size. Abdominal computed tomography showed an 11 × 10 cm mass in the right kidney. A laparoscopic right nephrectomy was performed because cystic carcinoma of the kidney was suspected. Pathologically, the tumor was diagnosed as mucinous cystadenoma of the renal parenchyma. Eighteen months after resection, the disease has not recurred. Conclusion: Here, we experienced a case of a renal mucinous cystadenoma as a slowly enlarging Bosniak IIF complex renal cyst.